Cross-sectional seroprevalence surveys of SARS-CoV-2 antibodies in children in Germany, June 2020 to May 2021 - Sorg, Anna-Lisa; Bergfeld, Leon; Jank, Marietta; Corman, Victor; Semmler, Ilia; Görtz, Anna; Beyerlein, Andreas; Verjans, Eva; Wagner, Norbert; Von Bernuth, Horst; Lander, Fabian; Weil, Katharina; et al. (Nature Communications, 2022)
The rate of SARS-CoV-2 infections in children remains unclear due to many asymptomatic cases. We present a study of cross-sectional seroprevalence surveys of anti-SARS-CoV-2 IgG in 10,358 children recruited in paediatric hospitals across Germany from June 2020 to May 2021. Seropositivity increased from 2.0% (95% CI 1.6, 2.5) to 10.8% (95% CI 8.7, 12.9) in March 2021 with little change up to May 2021. Rates increased by migrant background (2.8%, 4.4% and 7.8% for no, one and two parents born outside Germany). Children under three were initially 3.6 (95% CI 2.3, 5.7) times more likely to be seropositive with levels equalising later. The ratio of seropositive cases per recalled infection decreased from 8.6 to 2.8. Since seropositivity exceeds the rate of recalled infections considerably, serologic testing may provide a more valid estimate of infections, which is required to assess both the spread and the risk for severe outcomes of SARS-CoV-2 infections.